National, Regional, State, and Selected Local Area Vaccination Coverage Among Adolescents Aged 13–17 Years — United States, 2019 - Elam-Evans, Laurie D.; Yankey, David; Singleton, James A.; Sterrett, Natalie; Markowitz, Lauri E.; Williams, Charnetta L.; Fredua, Benjamin; McNamara, Lucy; Stokley, Shannon (MMWR. Morbidity and mortality weekly report, 2020)
Three vaccines are recommended by the Advisory Committee on Immunization Practices (ACIP) for routine vaccination of adolescents aged 11-12 years to protect against 1) pertussis; 2) meningococcal disease caused by types A, C, W, and Y; and 3) human papillomavirus (HPV)-associated cancers (1). At age 16 years, a booster dose of quadrivalent meningococcal conjugate vaccine (MenACWY) is recommended. Persons aged 16-23 years can receive serogroup B meningococcal vaccine (MenB), if determined to be appropriate through shared clinical decision-making. CDC analyzed data from the 2019 National Immunization Survey-Teen (NIS-Teen) to estimate vaccination coverage among adolescents aged 13-17 years in the United States.* Coverage with ≥1 dose of HPV vaccine increased from 68.1% in 2018 to 71.5% in 2019, and the percentage of adolescents who were up to date† with the HPV vaccination series (HPV UTD) increased from 51.1% in 2018 to 54.2% in 2019. Both HPV vaccination coverage measures improved among females and males. An increase in adolescent coverage with ≥1 dose of MenACWY (from 86.6% in 2018 to 88.9% in 2019) also was observed. Among adolescents aged 17 years, 53.7% received the booster dose of MenACWY in 2019, not statistically different from 50.8% in 2018; 21.8% received ≥1 dose of MenB, a 4.6 percentage point increase from 17.2% in 2018. Among adolescents living at or above the poverty level,§ those living outside a metropolitan statistical area (MSA)¶ had lower coverage with ≥1 dose of MenACWY and with ≥1 HPV vaccine dose, and a lower percentage were HPV UTD, compared with those living in MSA principal cities. In early 2020, the coronavirus disease 2019 (COVID-19) pandemic changed the way health care providers operate and provide routine and essential services. An examination of Vaccines for Children (VFC) provider ordering data showed that vaccine orders for HPV vaccine; tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine (Tdap); and MenACWY decreased in mid-March when COVID-19 was declared a national emergency (Supplementary Figure 1, https://stacks.cdc.gov/view/cdc/91795). Ensuring that routine immunization services for adolescents are maintained or reinitiated is essential to continuing progress in protecting persons and communities from vaccine-preventable diseases and outbreaks.Three vaccines are recommended by the Advisory Committee on Immunization Practices (ACIP) for routine vaccination of adolescents aged 11-12 years to protect against 1) pertussis; 2) meningococcal disease caused by types A, C, W, and Y; and 3) human papillomavirus (HPV)-associated cancers (1). At age 16 years, a booster dose of quadrivalent meningococcal conjugate vaccine (MenACWY) is recommended. Persons aged 16-23 years can receive serogroup B meningococcal vaccine (MenB), if determined to be appropriate through shared clinical decision-making. CDC analyzed data from the 2019 National Immunization Survey-Teen (NIS-Teen) to estimate vaccination coverage among adolescents aged 13-17 years in the United States.* Coverage with ≥1 dose of HPV vaccine increased from 68.1% in 2018 to 71.5% in 2019, and the percentage of adolescents who were up to date† with the HPV vaccination series (HPV UTD) increased from 51.1% in 2018 to 54.2% in 2019. Both HPV vaccination coverage measures improved among females and males. An increase in adolescent coverage with ≥1 dose of MenACWY (from 86.6% in 2018 to 88.9% in 2019) also was observed. Among adolescents aged 17 years, 53.7% received the booster dose of MenACWY in 2019, not statistically different from 50.8% in 2018; 21.8% received ≥1 dose of MenB, a 4.6 percentage point increase from 17.2% in 2018. Among adolescents living at or above the poverty level,§ those living outside a metropolitan statistical area (MSA)¶ had lower coverage with ≥1 dose of MenACWY and with ≥1 HPV vaccine dose, and a lower percentage were HPV UTD, compared with those living in MSA principal cities. In early 2020, the coronavirus disease 2019 (COVID-19) pandemic changed the way health care providers operate and provide routine and essential services. An examination of Vaccines for Children (VFC) provider ordering data showed that vaccine orders for HPV vaccine; tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine (Tdap); and MenACWY decreased in mid-March when COVID-19 was declared a national emergency (Supplementary Figure 1, https://stacks.cdc.gov/view/cdc/91795). Ensuring that routine immunization services for adolescents are maintained or reinitiated is essential to continuing progress in protecting persons and communities from vaccine-preventable diseases and outbreaks.